2015
DOI: 10.1128/aac.04723-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Amphotericin B Deoxycholate, Amphotericin B Lipid Complex, and Liposomal Amphotericin B against Aspergillus fumigatus

Abstract: Amphotericin B is a first-line agent for the treatment of invasive aspergillosis. However, relatively little is known about the pharmacodynamics of amphotericin B for invasive pulmonary aspergillosis. We studied the pharmacokinetics (PK) and pharmacodynamics (PD) of amphotericin B deoxycholate (DAMB), amphotericin B lipid complex (ABLC), and liposomal amphotericin B (LAMB) by using a neutropenic-rabbit model of invasive pulmonary aspergillosis. The study endpoints were lung weight, infarct score, and levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…The in vitro PK/PD index for L-AMB is higher than the corresponding index for conventional AMB (C-AMB) previously found in the same model (0.31 versus 0.15) (24), indicating that higher L-AMB than C-AMB concentrations are required for the same effect. A similar observation was found in an in vitro static model of human alveoli and in animal models, indicating that some of the active compound is locked in the liposome, rendering it inert (25,26). Interestingly, the PK/PD index of L-AMB determined in the present study (tC max /MIC, 31, taking into account the ϳ1% f u ) was similar to the PK/PD index determined in the static model (tC max /MIC, 31.04) in the alveolar compartment where conidia were inoculated and drug diffused into it from the endovascular compartment via the endothelial/alveolar cell lines.…”
supporting
confidence: 79%
“…The in vitro PK/PD index for L-AMB is higher than the corresponding index for conventional AMB (C-AMB) previously found in the same model (0.31 versus 0.15) (24), indicating that higher L-AMB than C-AMB concentrations are required for the same effect. A similar observation was found in an in vitro static model of human alveoli and in animal models, indicating that some of the active compound is locked in the liposome, rendering it inert (25,26). Interestingly, the PK/PD index of L-AMB determined in the present study (tC max /MIC, 31, taking into account the ϳ1% f u ) was similar to the PK/PD index determined in the static model (tC max /MIC, 31.04) in the alveolar compartment where conidia were inoculated and drug diffused into it from the endovascular compartment via the endothelial/alveolar cell lines.…”
supporting
confidence: 79%
“…If well tolerated, the use of higher targets may result in additional antifungal activity. These target values are predicted to result in antifungal activity that matches or exceeds that induced by other licensed agents for invasive aspergillosis, such as posaconazole, isavuconazole, and liposomal amphotericin B ( 8 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…73 Approximately 50 years after the discovery of liposomes, the FDA approved 13 liposome-based products for human 80 and pulmonary aspergillosis. 81,82 However, in 2013, Ariano et al 83 reported that L-AmB may not be adequate to control lung infections by Blastomyces dermatitidis. Al Nakeeb et al 82 found that lipid formulations of AmB can induce dose-dependent reduction in lung injury markers and circulating fungal biomarkers.…”
mentioning
confidence: 99%
“…81,82 However, in 2013, Ariano et al 83 reported that L-AmB may not be adequate to control lung infections by Blastomyces dermatitidis. Al Nakeeb et al 82 found that lipid formulations of AmB can induce dose-dependent reduction in lung injury markers and circulating fungal biomarkers. The recommended therapeutic dosages are 3-6 mg/kg/d.…”
mentioning
confidence: 99%
See 1 more Smart Citation